Risk Factors in Financial Services Industry: Application, Threats, Theoretical and Empirical literature in Management of Risk - Al-Qaisi, Khaldoun M.; Al-Batayneh, Rafat M. (International Journal of Economics and Financial Issues, 2018)
The purpose of this paper is to provide a critical study over enterprise risk management. For this, the paper has reviewed theoretical and empirical literature in management of risk. Theoretical literature depicts that no theory can explain about the risk management techniques alone. While empirical literature providesthe importance of enterprise risk management to be used in the organization for managing the risk, exist in portfolio structure of the organization. The paper besides that also provides theoretical and empirical literature and depicts about the effect on working of the organization by implementing the enterprise risk management. The paper has discussed many theories on the implications on organization. The paper briefly discusses about how the performance of organization structure, firm value, default risk perspective, and disclosure requirement would be affected due to implication of enterprise risk management model. The paper has discussed the importance of techniques like correlation, descriptive analysis and regression analysis. At last, the paper provides some recommendations, due to inconsistency in provided theories. For this, the paper considers present and future market conditions to lead to more development in enterprise risk management. Keywords: Risk, Risk Management, Risk Factors, Enterprise Risk Management. JEL Classifications: G00; G11; G31